F24 Design of a prospective, longitudinal, natural history study in huntington's disease. (September 2018) - Hooper, Gregory; Trundell, Dylan; Palermo, Giuseppe; Kremer, Thomas; Frick, Elsbeth; Boak, Lauren; ,; Doody, Rachelle; Schobel, Scott
Abstract : Background: With the advent of huntingtin protein-lowering therapies and the ability to measure mutant huntingtin protein (mHTT) in cerebrospinal fluid (CSF), there is a need to better understand the potential of CSF mHTT as a biomarker for predicting and measuring Huntington's disease (HD) progression. Observational studies including HD-Clarity and UCL-CSF aim to fill this knowledge gap but CSF is only collected once every 1- or 2-years, respectively, leaving unexplored the shorter-term timecourse of CSF mHTT and associated change in biological and clinical outcome measures. Aim: We are conducting a Natural History study with a primary objective to determine the relationship between CSF levels of mHTT, clinical measures of HD progression, markers of neuronal injury and brain atrophy over 15 months. Methods/Results: This prospective, longitudinal, multi-site Natural History study will follow patients with early manifest HD (Stage I or II). Clinical outcome measures will include composite Unified Huntington's Disease Rating Scale (cUHDRS), Total Functional Capacity (TFC), Total Motor Score (TMS), Symbol Digit Modalities Test (SDMT), and Stroop Word Reading (SWR) test. Other assessments include the measurement of CSF levels of mHTT, blood biomarkers and brain imaging. The utility of clinical outcome measures collected via sensors in smartphones and wrist-worn wearables will be assessed. CSF will be collected at four time points, namely, baseline, 3, 9 and 15 months. Conclusion: This study will provide valuable information on the relationship between putative biomarkers, including mHTT, and clinical outcomes in HD. It is expected to aid interpretation of future clinical trials. Funded by F. Hoffmann-La Roche.